Shoulder pain among high-level volleyball players and preseason features - Forthome, B.; Wieczorek, V.; Frisch, A.; Crielaard, J.-M.; Croisier, J.-L. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The main goal of this prospective study was to identify the most significant intrinsic risk factors for shoulder pain by measuring strength developed by shoulder rotators and by carrying out various morphostatic assessments.